Study of induction of labour with vaginal misoprostol in a tertiary hospital in a rural area of Telangana, India - Kothapally, Kavitha Reddy; Kavati, Vasantha; Bongu, Vydehi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The present study aims at the analysis of obstetric outcome of induction of labour with 25 µg of vaginal misoprostol in pregnancies beyond 36 weeks of gestation with unfavourable cervices. Methods: The present observational study was conducted at Bhaskar medical college & general Hospital, Yenkepally, Telangana from march 2014 to October 2014. 116 pregnant women were enrolled into the study based on appropriate indication for labour induction with 25 µg of vaginal misoprostol inserted fourth hourly till maximum of four doses or till the desired response was obtained. Results: Common indications for induction were postdatism (50.86%), pregnancy induced hypertension (PIH-19.82%), premature rupture of membranes (PROM-14.66%) & oligohydramnios (14.66%). Poor Bishop score of less than 4 was seen in 66.38% of cases. Normal vaginal delivery occurred in 60 cases (51.72%) against Lower Segment Cesarean Section (LSCS) for various reasons in 56 cases (48.28%). Successful induction, measured as onset of active labour (3 contractions in 10 min with duration of 40 sec of each contraction) or cervical dilatation of 3 cm or successful vaginal delivery, was seen in 107 (92.24%) cases. Failed induction measured as no cervical changes or no onset of labour pains even after 4 doses of vaginal misoprostol was seen in 9 cases (7.76%). Out of 60 successful vaginal deliveries 2 doses of misoprostol was required in 27 cases (45%) & 1 dose was required in 29 cases (48.33%). Induction delivery interval of 7-12 hours was seen in 26 cases (43.33%). Maternal complications were seen in 27 cases (23.28%), common ones being postpartum haemorrhage (PPH) & PROM. No case of uterine hyperstimulation or rupture was seen. In 113 cases (97.41%), 5 min APGAR score was more than 7. Neonatal Intensive Care Unit (NICU) admissions in the newborn was 4 (3.45%). Conclusions: Hence labour induction with 25microgms of vaginal misoprostol in pregnancies with unfavourable cervices improves Bishop’s score, reduces induction delivery interval, reduces caesarean section rates & does not affect fetal outcome.